Contribution of Cooperative Societies to Credit Access, Investment Activities, and Enterprise Growth among Members in Kaduna State, Nigeria (Nigerian Journal of Cooperative Economics and Management, 2026)
This study examined the contribution of cooperative societies to credit access, investment activities, and enterprise growth among members in Kaduna State, Nigeria. The study adopted a descriptive survey research design and utilised primary data collected through structured questionnaires administered to 384 members of agricultural, consumer, and multipurpose cooperative societies across Kaduna State, of which 371 questionnaires were returned and found valid, representing a response rate of 96.6%. Data collected were analysed using descriptive statistics, Pearson correlation, and ordinary least squares (OLS) regression analysis. The findings revealed that cooperative society engagement significantly predicts members' access to credit (β = 0.534, R² = 0.487, F = 69.74, p < 0.05) through affordable loan schemes, flexible repayment conditions, and reduced collateral requirements. Cooperative engagement also significantly predicts investment activities (β = 0.498, R² = 0.461, F = 49.87, p < 0.05), and enterprise growth (β = 0.521, R² = 0.503, F = 59.77, p < 0.05). Regression diagnostic tests confirmed residual normality, homoscedasticity, and absence of autocorrelation across all three models. The study concludes that cooperative societies are important institutional vehicles for improving credit access, stimulating productive investment, and supporting enterprise growth among members in Kaduna State. The study recommends improved credit administration, investment-support programmes, and enterprise development initiatives to strengthen the economic contributions of cooperative societies among members.
Keywords: Cooperative societies; credit access; investment activities; enterprise growth; Kaduna State; Nigeria